Effect of β-Propiolactone Inactivation of Polyoma Virus on Viral Functions - Brown, A. (1974)
Polyoma virus was inactivated by treatment with β-propiolactone. T-antigen production, polyoma-RNA synthesis, induction of host DNA synthesis (measured by incorporation of labeled thymidine into the cell culture), and in vitro transforming ability were inactivated to a similar degree by various β-propiolactone concentrations (0.25% β-propiolactone reduced these functions approximately 96%), whereas plaque-forming ability and the ability of the virus to replicate its DNA and to synthesize capsid antigen were inactivated by a given concentration of β-propiolactone to a much greater degree (0.25% β-propiolactone led to a reduction of plaque-forming ability of over 8 logs). The significance of these data and their relationship to previously published experiments are discussed.